Detection of Land Use and Land Cover from an Optical Remote Sensing Image: A Review - A. V. Kavitha; A. Srikrishna (Techniques and Innovation in Engineering Research Vol. 1, 2022)
Since the inception of a remote sensing image, the detection of land use and land cover from an optical image has been a crucial study topic. Maps of land use and cover are widely used in agriculture, environmental monitoring, urban planning, and other fields, as well as in the management of various catastrophic disasters like floods, tsunamis, and forest fires. The main methods for identifying land use and land cover from an optical remote sensing image were examined in this research. The value of strategies based on spatial context and mathematical morphology has finally been argued after many techniques based merely on spectral information, spatio-contextual information, and knowledge-based methods have all been examined.